2020
DOI: 10.1002/cssc.202002113
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Degradation Mechanism of NCM523Graphite Lithium‐Ion Full Cells Operated at High Voltage

Abstract: Layered oxides, particularly including Li[NixCoyMnz]O2 (NCMxyz) materials, such as NCM523, are the most promising cathode materials for high‐energy lithium‐ion batteries (LIBs). One major strategy to increase the energy density of LIBs is to expand the cell voltage (>4.3 V). However, high‐voltage NCM∥ graphite full cells typically suffer from drastic capacity fading, often referred to as “rollover” failure. In this study, the underlying degradation mechanisms responsible for failure of NCM523∥ graphite full ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
104
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 91 publications
(293 reference statements)
11
104
0
Order By: Relevance
“…These domains are validated in our previous publication and could be attributed to Li dendrites by means of, for example, microscopic techniques and Li NMR. [ 20 ] Moreover, these Li metal dendrites are obviously formed at the same spots, where TM previously deposit, as they are located at identical spots as shown in the SEM‐EDX analysis for Co, Mn, and Ni. Interestingly, the graphite‐based anode cycled in the EC‐free electrolyte is free of these spots based on TMs and Li metal dendrites.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…These domains are validated in our previous publication and could be attributed to Li dendrites by means of, for example, microscopic techniques and Li NMR. [ 20 ] Moreover, these Li metal dendrites are obviously formed at the same spots, where TM previously deposit, as they are located at identical spots as shown in the SEM‐EDX analysis for Co, Mn, and Ni. Interestingly, the graphite‐based anode cycled in the EC‐free electrolyte is free of these spots based on TMs and Li metal dendrites.…”
Section: Resultsmentioning
confidence: 67%
“…It is known, that the roll‐over fading is the result of the electrode cross‐talk, that is, TM dissolution from the cathode and transport to and deposition on the anode. [ 20 ] The cathode, as obvious initiator of this failure, can be modified by, for example, literature well‐known coating with Al 2 O 3 . [ 41–43 ] Indeed the coating can prolong the cycle life but still cannot prevent the sudden roll‐over fading (here: cycle no.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells operated at 4.5 V show an early induced ‘rollover’ failure after ≈50 cycles, caused by TM deposition (Ni, Mn, Co), significant SEI growth and Li metal dendrite formation, which subsequently results in the generation of (micro‐)short‐circuits, as discussed in a previous work. [ 11 ] In contrast, the LIB cells operated at 4.3 V do not show any rollover failure and a rather stable capacity over 100 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…This surface layer is clearly the reason for the poor performance even compared to the reference electrolyte. A recent study revealed impedance growth on the positive electrode and especially transition metal dissolution from its active material to be the predominant reasons for capacity fading and in some cases even rapid cell failure, known as “rollover” failure, in NMC532‖graphite cells under high voltage conditions [34] . In line with this, the formation of an effective CEI by the studied phospholane functional additives evidently alters these processes and is thus beneficial for an enhanced battery performance.…”
Section: Resultsmentioning
confidence: 75%